Altered Serum Oxytocinase and Enkephalin-Degrading Aminopeptidase Activities in Patients With Fibromyalgia. Issue 4 (July 2019) - Martínez-Martos, José Manuel; Correa-Rodríguez, María; Rus, Alma; Molina, Francisco; Ramírez-Expósito, María Jesús; Aguilar-Ferrandiz, María Encarnación
Objectives: Fibromyalgia (FM) is a chronic pain condition of unclear etiology. We have analyzed, for the first time, the activity of a broad spectrum of aminopeptidases (APs) in patients with FM and controls to investigate whether they are involved in the pathophysiology of this syndrome. Method: In this case–control study, we fluorometrically measured specific AP activities in serum samples of 75 patients with FM and 29 healthy controls. The predictive value of AP activities in FM was determined by receiver operating characteristic (ROC) analysis. Results: Oxytocinase activity was higher in patients with FM than in controls ( p < .001). A subgroup of patients with FM ( n = 18; 24%) showed low levels of enkephalin-degrading aminopeptidase (EDA) activity when compared with the healthy controls ( p < .001) and with the rest of FM patients ( p < .001). There were no significant differences in the activity levels of aminopeptidase A, aminopeptidase B, aspartyl aminopeptidase, insulin-regulated aminopeptidase, pyroglutamyl aminopeptidase, or aminopeptidase N between FM patients and controls. According to ROC analysis, oxytocinase activity may be a good marker for differentiating individuals with FM from healthy subjects. Conclusions: Our findings show that serum oxytocinase activity is increased in patients with FM, which could alter the metabolism of peptides with analgesic effects such as oxytocin and enkephalins. The determination of serum oxytocinase activity may aid in FM diagnosis. Additionally, we have identified a subpopulation of FM patients with abnormally low serum EDA activity.